The asymmetric dominance effect and beer brands - Sun, William (2020)
This study aims to explore in which situations the asymmetric dominance effect might happen or not. Some authors suggest that the effect only happen in very rare occasions, where the stimuli is quantitative and clear. As for qualitative stimuli, the effect is diminished and practically vanishes. The main reason is that qualitative stimuli, such as perception of image quality or brands, rely on subjective interpretation. The present study investigates the effect using three beer brands and measures an individual’s brand preference using consumerbased brand equity (CBBE). The choice set is constructed in a way that the most preferred brand is set at a higher price, the second option as the target and at the same price as the third option, the decoy. In this case, the decoy effect would happen if respondents choose the second preferred option. Essentially, the key question here is to understand if the effect would happen given different levels of brand preference. Results showed that the effect was not observable (p-value not significant at 5% but significant at 10%). In addition, brand preference measurements were not good predictors for the targeted option. However, when it comes to overall choice, brand preference was a good predictor of choice. The results serve as initial thoughts of investigating the effect using a metric to measure how respondent perceive certain qualitative stimuli.